The Composite Nickel Hydroxide / Activated Carbon as Electrode Material in the Battery Storage Devices - Khemiy О.M.; Budzulyak І.М.; Morushko, O.V.; Stubrov, Yu.Yu.; Yaremiy, I.P.; Yablon, L.S. (Physics and Chemistry of Solid State, 2015)
The paper presents the results of studies of the structure and electrochemical properties of composite β-Ni(OH)2/C. It is shown that the diffractograms composite sintered β-Ni(OH)2/C in addition to peaks characteristic NiO, there is a broad diffraction peak at 23 °, which can be attributed to the activated carbon. Found that the composite electrode based on β-Ni(OH)2/C has a specific capacity, which is almost 25 times higher than the capacity for the output of nickel hydroxide at a current of 1 mA.